Simmel, the Emotions and the Tragic Nature of the Love Bond - Cerulo, Massimo (Simmel Studies, 2021)
The aim of this essay is to analyze the sociological study of emotions produced by Georg Simmel, with specific attention to the concept of love. The article is structured as follows: in the first part, what could be defined as ‘Simmel's sociology of emotions’ is presented through a descriptive and interpretative analysis of the constructed social theory; in the second part, the focus shifts to love as emotion, emphasizing its tragic character within the construction and destruction of the social bond. Finally, in the third part, a comparison with the sociological analysis of love produced by two contemporary researchers such as Eva Illouz – love as a result of the dynamics conveyed by ‘emotional capitalism’ – and Danilo Martuccelli – love as an ‘emotional imperative’ of contemporary daily life - will be produced. The common thread of the entire essay is exactly the tragic character of the emotion of love, which allows both the construction and the destruction of the social bond, through an ambivalent interactional game that seems to have no end.